PENGGUNAN GUM XANTHAN PADA SUBSTITUSI PARSIAL TERIGU DENGAN TEPUNG JAGUNG DALAM PEMBUATAN ROTI [Use of Xanthan Gum in Partial Substitusion of Corn Flour for Wheat Flour in Breadmaking] - Posman Sibuea (Jurnal Teknologi dan Industri Pangan, 2001)
The objective of the experiment was to examine the capabilities of composite flour (i.e. corn flour and wheat flour) and xanthan gum in breadmaking. Breads were produced using mixture of wheat and corn flour at varios ratio with addition of xanthan gum at different level (0.0% to 0.75%). The result showed that the composite flour had significant effect on all measured parameters. As the wheat flour descreaseed down to 65% the dought length, texture, reducing sugar content increased, but the sensory values descresed, xanthan gum had significant effect on the texture, reducing sugar content, the sensory values and the dough length. As the xanthan gum increased, the dough length, the reducing sugar content increased, whereas the texture increased at 0.50% the descreased at 0.75%. the bread of good acceptability was produced from the floaur mixture of wheat flour (70%) and corn flour (30%) using 0.75% of xanthan gum.